EVALUATING THE ROLE OF SCAPULA MORPHOLOGY IN ROTATOR CUFF TEARS: WHICH IS THE MOST USEFUL PREDICTOR? - Karademir, Gokhan; Tunali, Onur; Atalar, Ata (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2021)
Objective: The aim of this study was to determine the relation-ships between glenoid inclination (GI), acromial index (AI), criti-cal shoulder angle (CSA), superior inclination (SI), and symptom-atic degenerative full-thickness supraspinatus tears (SSTs).Materials and Methods: Patients who were diagnosed with SSTs (n=39) between 2015 and 2017 were assessed retrospec-tively. Controls were matched to age, gender, and side. Mea-sured GI, AI, CSA, and SI values were compared between the SSTs and control groups (n=39). The mean age for the SSTs group was 52.74 +/- 5.49 years, and the mean age for the control group was 51.15 +/- 5.22 years.Results: The mean GI for the SSTs group was 19.97 degrees +/- 5.62 degrees, and it was 13.72 degrees +/- 6.55 degrees for the control group (p<0.001). The mean AI was 0.7 +/- 0.08 and 0.67 +/- 0.07 in the SSTs and control groups, respectively (p=0.035). The mean CSA for the SSTs group was 35.05 degrees +/- 4.09 degrees and it was 33.06 degrees +/- 3.42 degrees for the control group (p=0.022). The mean SI was 25.13 degrees +/- 5.71 degrees and 25.91 degrees +/- 5.81 degrees in the SSTs and control groups, respectively (p=0.552). For a cut-off value of GI 217.35 degrees, sensitivity was 79.54\%, and specificity was 79.51\% (p=0.001). For a cut-off value of AI 20.67, sensitivity was 61.54\% and specificity was 56.4\% (p=0.031). For a cut-off value of CSA 233.45 degrees, sensitivity was 64.12\%, and specificity was 64.54\% (p=0.014).Conclusion: Higher measurement values of glenoid inclination, acromial index, and critical shoulder angle were associated with symptomatic degenerative full-thickness supraspinatus tears, and no correlation was found with superior inclination measure-ment. The glenoid inclination measurement had the highest sensitivity and specificity in predicting symptomatic degenera-tive full-thickness supraspinatus tears.
Keywords: Acromial index; critical shoulder angle; glenoid incli-nation; rotator cuff tear; superior inclination